PENGARUH EDUKASI BOOKLET TENTANG KEBUTUHAN GIZI BALITA TERHADAP PENGETAHUAN IBU BALITA GIZI KURANG - Suryati Suryati; Nurjanah Nurjanah; Eni Setyaningsih (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2018)
Background: One of the causes of nutritional problems in children under five is low nutrition knowledge in mothers or caregivers. Low maternal knowledge about nutrition can lead to poor food intake, type and quality, so that the incidence of acute malnutrition can increase. Knowledge of low food diversity such as food selection is not in accordance with nutritional needs of toddlers, around 59% of families have not applied a diverse diet to toddlers.   Objective: To find out the effect of nutritional education by using booklet media on maternal knowledge about nutrition for malnourished children under five in the working area of Pundong Bantul Health Center Yogyakarta   Methods: This study used a quasi experimental method, with pre and post test without control group design. The sample in this study were mothers with underweight nutrition with a total of 44 respondents. The sampling technique used was simple random sampling. Analysis of the study using Wilcoxon statistical test to determine differences in knowledge between pretest and posttest.   Results: The results of pretest and posttest knowledge of mothers given booklet education showed a statistically significant increase with p value of 0.001 (p 0.05). Booklet education as an effective communication method can improve maternal knowledge about the nutritional needs of children.  Conclusion: There is an effect of booklet education on maternal nutrition of undernourished children and there is a significant difference between the nutritional knowledge scores of mothers